Method and apparatus for remotely changing flow profile in conduit and drilling bit - Tahoun, Ahmed; Kafafy, Raed; Jawamir, Karam; Mohammed Aldheeb, Mohammed Abdulmalek; Khalil, Abdul Mushawwir (2016)
An apparatus and method for remotely adjusting the hydraulic horse power per square inch (HSI) of a drill bit. The apparatus and method may allow the nozzle geometry to be varied remotely without the need to pull the drill string outside the hole. This nozzle may include a body configured to be secured within the rotary drill bit, and a fluid passage within that body that leads to an orifice. The geometry of the fluid passage may be variable, and varying it may result in a change in the nozzle HSI; this may allow drilling different rock formations to be optimized in different drilling environments. Different placements of the nozzle, such as within the inner flow passage or between the inner flow passage and annular flow passage for controlling flow profile within a wellbore, a tubular string or a flow conduit, may be envisioned.